The role of calcium metabolism in Plasmodium falciparum - Kirchmann, Nicola Helen (My University, 2014)
Very little is known about how the malaria parasite regulates calcium levels, but it is of undoubted importance as calcium is one of the key intracellular messengers relaying both physiologic and plasmacological signals. The aim of this study was to establish resistance reversal properties of flunarizine and fluoxetine and to gain a deeper understanding of the role of calcium metabolism in Plasmodium falciparum. The effects of the resistance modulators, flunarizine and fluoxetine were, examined in vitro on the chloroquine-resistant (FCR-3) and chloroquine-sensitive (3D7-A) strains of Plasmodium falciparum in combination with chloroquine, quinine and mefloquine. Both flunarizine and fluoxetine were found to have intrinsic antimalarial activity. These studies revealed that both flunarizine and fluoxetine reverse both chloroquine and quinine resistance in the FCR-3 strain and produce only an additive effect in the 3D7-A strain. Both the FCR-3 and 3D7-A strains were seusitive to mefloquine. A combination of the resistance modulators and mefloquine produced a synergistic effect in both strains. Calcium homeostasis studies confirmed that there is an increased influx and decreased efflux of calcium in parasitised red blood cells compared to unparasitised red blood cells. This increased calcium content is localised in the parasite compartment. Extracellular calcium is necessary for erythrocyte invasion by the merozoite and for subsequent development and maturation of the parasite within the erythrocyte. The classic antimalarials, chloroquine and quinine, as well as the resistance reve.'sal agents,flunarizine and fluoxetine, at IC3 concentrations, block calcium uptake into the parasitised red blood cells (pRBC). Additionally, there is no significant difference in cnloiam influx and efflux between th e chloroquine-resistant (FCR-3) and chlcloquine-sensitive (3D7-A) strains of Plasmodium falciparum.